Discretion, community, and correctional ethics - Kleinig, John, 1942-; Smith, Margaret Leland (Rowman & Littlefield Publishers, 2001)
Is it possible to develop and instill a professional ethic for prison personnel that, in partnership with formal regulatory constraints, will mediate relations among officers, staff, and inmates, or are the failures of imprisonment as an ethically-constrained institution so deeply etched into its structure that no professional ethic is possible? The contributors to this volume struggle with this central question and its broader and narrower ramifications.